Раннесредневековые храмы западной части Херсонеса - Завадская, И.А. (Материалы по археологии, истории и этнографии Таврии, 1998)
This article is an attempt to show the main periods of cult building in the western part of Chersonesos on the basis of archaeological material. Early-medieval temples -Basilica on the hill, Western basilica, four-apsed temple- sprang in one chronological period, not earlier the second quarter of the 6th century and not later than the first half of the 7th century. Their destruction is dated back to the end of the 10th - the first quarter of the 11th centuries. Perhaps, this event could be connected with the campaign of Prince Vladimir to Cherson in 988-989. After destroying early medieval temples, cult plots, except the territory of the Western basilica were not neglected. On the ruins of early Basilica on the hill they built a new temple complex.There were some attempts to restore four -apsed temple. A small chapel appeared in the place of Western-Zagorodnyfin the outskirts of the town) the destruction of which is also associated with the campaign of Prince Vladimir.